Alcune osservazioni sui saggi "Russia" (1910) e "Santa Russia" (1918) di Andrej Belyj (ENTHYMEMA, 2023)
Andrei Bely (1880-1934), one of the leading exponents of Russian Symbolism, dealt with the theme of Russia in many of his works. Of these, the essay "Russia" (1910), atypical of the corpus of his works due to the absence of the usual mystical orientation and because of the almost didactic clarity of the structure, has remained somewhat in the shadows in the very extensive studies on the author. The aim of this work is to highlight its structure and rhetorical strategies, also on the basis of a comparison with other works by Bely, in particular the essay "The Saint Russia" (1918), which, appearing eight years after the first publication of "Russia", is in direct dialogue with the 1910 essay.
Keywords: Andrei Bely; Russian Literature